Cecal CircRNAs Are Associated With the Response to Salmonella Enterica Serovar Enteritidis Inoculation in the Chicken - Zheng, Linna; Liu, Liying; Lin, Lili; Tang, Hui; Fan, Xinzhong; Lin, Hai; Li, Xianyao (Frontiers in Immunology, 2019)
Circular RNAs (circRNAs) are a class of endogenous noncoding RNA, which is different from linear RNA. CircRNA is an RNA molecule with a closed loop structure formed by reverse splicing. CircRNAs have been studied in several organisms, however, the circRNAs associated with the response to Salmonella enterica serovar Enteritidis (SE) inoculation in chickens are still unclear. In the current study, Jining Bairi chickens were inoculated with SE. CircRNAs involved in the response to SE inoculation were identified through next-generation sequencing. Our results showed that there were 5,118 circRNAs identified in the control and treated groups. There were 62 circRNAs significantly differentially expressed following SE inoculation. Functional classification revealed that those significantly differentially expressed circRNAs were associated with immune system process, rhythmic process and signaling following SE inoculation. CircRNAs NC_006091.4: 65510578|65515090, NC_006099.4: 16132825|16236906 and NC_006099.4: 15993284|16006290 play important roles in the response to SE inoculation. The findings in the current study provide evidence that circRNA alterations are involved in the response to SE inoculation in the chicken.